Mitochondrial Dysfunction in Cardiorenal Syndrome 3: Renocardiac Effect of Vitamin C - Raquel Silva Neres-Santos; Carolina Victoria Cruz Junho; Karine Panico; Wellington Caio-Silva; Joana Claudio Pieretti; Juliana Almeida Tamashiro; Amedea Barozzi Seabra; César Augusto João Ribeiro; Marcela Sorelli Carneiro-Ramos (Cells, 2021)
Cardiorenal syndrome (CRS) is a pathological link between the kidneys and heart, in which an insult in a kidney or heart leads the other organ to incur damage. CRS is classified into five subtypes, and type 3 (CRS3) is characterized by acute kidney injury as a precursor to subsequent cardiovascular changes. Mitochondrial dysfunction and oxidative and nitrosative stress have been reported in the pathophysiology of CRS3. It is known that vitamin C, an antioxidant, has proven protective capacity for cardiac, renal, and vascular endothelial tissues. Therefore, the present study aimed to assess whether vitamin C provides protection to heart and the kidneys in an in vivo CRS3 model. The unilateral renal ischemia and reperfusion (IR) protocol was performed for 60 min in the left kidney of adult mice, with and without vitamin C treatment, immediately after IR or 15 days after IR. Kidneys and hearts were subsequently collected, and the following analyses were conducted: renal morphometric evaluation, serum urea and creatinine levels, high-resolution respirometry, amperometry technique for NO measurement, gene expression of mitochondrial dynamic markers, and NOS. The analyses showed that the left kidney weight was reduced, urea and creatinine levels were increased, mitochondrial oxygen consumption was reduced, NO levels were elevated, and Mfn2 expression was reduced after 15 days of IR compared to the sham group. Oxygen consumption and NO levels in the heart were also reduced. The treatment with vitamin C preserved the left kidney weight, restored renal function, reduced NO levels, decreased iNOS expression, elevated constitutive NOS isoforms, and improved oxygen consumption. In the heart, oxygen consumption and NO levels were improved after vitamin C treatment, whereas the three NOS isoforms were overexpressed. These data indicate that vitamin C provides protection to the kidneys and some beneficial effects to the heart after IR, indicating it may be a preventive approach against cardiorenal insults.